2015
DOI: 10.1007/978-3-662-48797-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Security Proofs in Lattice-Based Cryptography: Using the Rényi Divergence Rather Than the Statistical Distance

Abstract: Abstract. The Rényi divergence is a measure of closeness of two probability distributions. We show that it can often be used as an alternative to the statistical distance in security proofs for lattice-based cryptography. Using the Rényi divergence is particularly suited for security proofs of primitives in which the attacker is required to solve a search problem (e.g., forging a signature). We show that it may also be used in the case of distinguishing problems (e.g., semantic security of encryption schemes),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 25 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…We use Rényi Divergence (RD) in our analysis, relying on techniques developed in [41,38,9]. For any two probability distributions P and Q such that the support of P is a subset of the support of Q over a countable domain X, we de ne the RD (of order 2) by R(P Q) = x∈X P (x) 2 Q(x) , with the convention that the fraction is zero when both the numerator and denominator are zero.…”
Section: Rényi Divergencementioning
confidence: 99%
“…We use Rényi Divergence (RD) in our analysis, relying on techniques developed in [41,38,9]. For any two probability distributions P and Q such that the support of P is a subset of the support of Q over a countable domain X, we de ne the RD (of order 2) by R(P Q) = x∈X P (x) 2 Q(x) , with the convention that the fraction is zero when both the numerator and denominator are zero.…”
Section: Rényi Divergencementioning
confidence: 99%
“…These fundamental limits are indexed by the Rényi parameter. Our work is also partly motivated by Shikata [18] who quantified lengths of secret keys in terms of Rényi entropies of general orders and Bai et al [19] who showed that the Rényi divergence is particularly suited for simplifying some security proofs. Furthermore, it is worth noting that it is quite natural to use various divergences to measure the discrepancy between two distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The closeness of two distribution can be measured through many methods. Among them, Rényi divergence is a well-known method, which is parameterized by a real a > 1 and defined for two distributions P and Q as follows [23], [24]. where sup(P ) represents the support of P and Q(x) = 0 for x ∈ sup(P ).…”
Section: Closeness Of Centered Binomial Distribution and The Correspomentioning
confidence: 99%